Pengaruh Siritual Religious Coping Terhadap Loss Griefing Trauma Penyintas COVID-19 - Priyantini, Diah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Coronavirus Disease 2019 (COVID-19) has a deep traumatic effect with high cases and deaths, thus causing survivors to experience a mental health crisis and reduced resilience. The purpose of this research is to analyze the influence of spiritual religion on the loss griefing trauma of COVID-19 survivors. This study used a quasy experimental design with a pre and post test control group design. A total of 110 respondents were recruited by purposive sampling and divided into control and intervention groups. The intervention group was given spiritual religious coping interventions and the control group was given according to the intervention so far. Then both groups were measured loss griefing trauma during the COVID-19 pandemic. Data were analyzed using the Wilcoxon test with SPSS version 21. The results showed that there was a significant influence of spiritual religious coping on loss griefing trauma. The level of loss griefing trauma showed a loss of 24.16%, bad feelings of 13.76%, lack of self-acceptance of 11.82% and severe to very large trauma conditions of 37.69%. The results of the study can be concluded that spiritual religious coping can be an effective intervention in dealing with loss griefing trauma in survivors of COVID-19.